CLIF-C AD score predicts survival benefit from pre-emptive TIPS in individuals with Child-Pugh B cirrhosis and acute variceal bleeding - Yong Lv; Wei Bai; Xuan Zhu; Hui Xue; Jianbo Zhao; Yuzheng Zhuge; Junhui Sun; Chunqing Zhang; Pengxu Ding; Zaibo Jiang; Xiaoli Zhu; Weixin Ren; et al. (JHEP Reports, 2022)
Background & Aims: Among individuals with Child-Pugh B cirrhosis and acute variceal bleeding (AVB), the Baveno VII workshop recommended pre-emptive TIPS in those with a Child-Pugh score of 8-9 and active bleeding at initial endoscopy (Child B8-9 + AB criteria). Nevertheless, whether this criterion is superior to the CLIF-Consortium acute decompensation score (CLIF-C ADs) remains unclear. Methods: Data on 1,021 consecutive individuals with Child-Pugh B cirrhosis and AVB from 13 university hospitals in China who were treated with pre-emptive TIPS (n = 297) or drug plus endoscopic treatment (n = 724) between 2010 to 2019 were retrospectively analysed. A competing risk regression model was used to compare the outcomes between the two groups after adjusting for confounders. The concordance-statistic for benefit (c-for-benefit) was used to evaluate a models’ ability to predict treatment benefit (risk difference between treatment groups). Results: Pre-emptive TIPS was associated with reduced mortality compared to drug plus endoscopic treatment (adjusted hazard ratio 0.62, 95% CI 0.44 to 0.88). A higher baseline CLIF-C AD score was associated with greater survival benefit (i.e., larger absolute mortality risk reduction). After adjusting for confounders, a survival benefit was observed in individuals with CLIF-C ADs ≥48 or Child-Pugh B8-9 with active bleeding, but not in those with CILF-C ADs <48, no active bleeding or Child-Pugh B7 with active bleeding. The c-for-benefit of CILF-C ADs for predicting survival benefit was higher than that of Child B8-9+AB criteria. Conclusions: In individuals with Child-Pugh B cirrhosis and AVB, CLIF-C ADs predicts survival benefit from pre-emptive TIPS and outperforms the Child B8-9+AB criteria. Prospective validation should be performed to confirm this result, especially for other aetiologies of cirrhosis. Impact and implications: In this study, among individuals with Child-Pugh B cirrhosis and acute variceal bleeding, the CLIF-Consortium acute decompensation (CLIF-C AD) score could predict the survival benefit from pre-emptive TIPS, with patients with higher CLIF-C AD scores benefiting more from pre-emptive TIPS. Furthermore, the CLIF-C AD score outperformed the Child B8-9 plus active bleeding criteria in terms of discriminating between those who obtained more benefit vs. less benefit from pre-emptive TIPS. Depending on prospective validation, the CLIF-C AD score could be used as the model of choice to determine who should undergo pre-emptive TIPS.